Nonalcoholic fatty liver disease and bariatric surgery: a comprehensive review - Cazzo, Everton (2017)
CONTEXT AND OBJECTIVE: Nonalcoholic fatty liver disease (NAFLD) has been increasingly diagnosed worldwide and is now recognized as a source of public health concern. It comprises a wide spectrum of histological features that range from simple steatosis to severe forms of fibrosis, steatohepatitis and even cirrhosis. The impact of bariatric surgery on the course of NAFLD in individuals with obesity has been extensively studied. DESIGN AND SETTING: Narrative review; public university hospital. METHODS: A comprehensive review was conducted based on an online search on the electronic databases MEDLINE and LILACS using the MeSH terms “fatty liver” and “bariatric surgery”. RESULTS: The exact mechanisms that lead to improvement in NAFLD following bariatric surgery are not completely understood. Since Roux-en-Y gastric bypass (RYGB) is the bariatric surgical procedure most performed worldwide, it is also the one from which the effects on NAFLD have been most studied, although there is also consistent evidence regarding the effects from gastric banding, sleeve gastrectomy and biliopancreatic diversions. CONCLUSION: According to the currently available evidence, bariatric surgery leads to significant improvement in NAFLD. Further research, especially by means of randomized controlled trials enrolling larger cohorts of individuals, is needed to determine the optimal procedure for this group of subjects.